High disease activity is associated with higher blood pressure in recent onset rheumatoid arthritis patients, post-hoc analyses of IMPROVED study. (11th May 2021) - Gegenava, M; Bergstra, SA; Maassen, H; Allaart, CF
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease with a high prevalence of cardiovascular morbidity and mortality. Purpose: purpose of our project was to investigate the association between disease activity and systolic and diastolic blood pressure (SBP, DBP) in patients with recent-onset rheumatoid arthritis (RA 2010 criteria) or undifferentiated arthritis (UA) who were treated to target disease activity score (DAS)<1.6 in the IMPROVED study. Methods: The associations between disease activity and SBP/DBP were tested for 610 patients (364 RA, 246 UA), cross-sectionally and over time. GEE analyses were performed with both SBP and DBP as outcome measures and disease activity categories (DAS<1.6;>1.6 but ≤2.4; >2.4), CRP level, treatment arms or the number of visits on a certain drug as potential predictors in separate analyses. Separate analyses tested potential contributions of gender, anti-cyclic citrullinated peptide antibodies (ACPA) status, and fulfilling the 2010 ACR/EULAR (American college of rheumatology/ European league against rheumatism) classification criteria. In addition association of BP with various levels of disease activity was tested with T-test. Results: At the baseline mean (SD) SBP was 133 (20) and DBP mean (SD) was 80 (10).  SBP > 140mm Hg was observed in 40% of patients and DBP > 90 mm Hg  in 21% of patients. SBP and DBP statistically significantly decreased during 5 years follow up (mainly during year 1), but the difference in mm Hg was small. Estimates from GEE analysis showed that patients with high DAS >2.4 (HDAS) had a statistically significantly higher SBP (average 3 mm Hg higher, 95% CI 1.7; 4.2, p < 0.01), than the patients in with DAS ≤2.4. ANOVA analyses showed a statistically significant association between SBP and DAS. In addition, post hoc analyses showed that patients with HDAS had a statistically significantly higher  SBP (mean (SD) 132 (19) than the patients with DAS < 1.6 (remission) (mean (SD) 129 (20), p < 0.01), and patients in LDAS but DAS≥1.6 had a statistically significantly higher SBP (mean (SD) 131 (19) than the patients in remission (mean (SD)  129 (20), p = 0.02) (Figure 1), whereas no association was found between DAS category and DBP. Gender, ACPA status or fulfilling the 2010 classification criteria did not influence the relation between DAS and blood pressure. Conclusions: In patients with RA or UA, a higher DAS is associated with higher blood pressure, but the clinical impact is unclear.